STRUCTURE AND GRAMMATICAL FUNCTION OF LEO LANGUAGE - Yudha, I Ketut; Artawa, Ketut; Meko Mbete, Aron; Sri Satywawati, Made (e-Journal of Linguistics; Vol. 5. Juli 2011 No. 2, 2011)
Lio language is a language spoken in Central Flores. Having limited morphological process in general and affixation process involving verbs (head marking) and nouns (dependent marking) in particular, it is classified into an isolating language. The studies exploring the languages spoken in the eastern part of Indonesia using Lexical Functional Grammar and the theory of typology are highly limited. In addition, Lio language is merely an isolating one and does not have cross referencing. It is this which inspired the writer to conduct research in syntax. This study aims at investigating the canonic structure, the types of verbs used as predicates, the grammatical function, the alternate of clausal structure, the mapping and the pivotance in Lio language. The results of analysis show that the clauses in Lio language can be divided into basic clauses with verbal and nonverbal predicates. The  predicates of the verbal clauses are classified into simple, serial, and causative.  The serial verbal constructions are distinguished based on the semantic features of the verbal components forming the serial verbal constructions. These types can be observed from the nature of the relationships among the components forming the serial verbal constructions. A serial verbal construction is made up of more than one verbs and behaves as a simple predicate. There is no dependence marker among the components forming the serial verb.  The causative structure also forms monoclause and biclause. The functional mapping uses the features [+/-r] and [+/-o], the argument uses the features [-r] and [-o] which are mapped to  SUBJ, [-r] and [+o] are mapped to OBJ, [+r] and [+o] are mapped to OBJ2 or OBJ? and [+r] and [-o] are mapped to OBL (Oblique). Lio language has GF SUBJ and OBJ as the nuclear GF (nuclear grammatical function), and OBL, COMP, and ADJ as the nonnuclear grammatical functions. The SUBJ appears before the verb (preverbal position) and the OBJ appears after the verb (postverbal position). Based on how the constituents are ordered, Lio language is an SVO and VOS language. Typologically, it is classified into an ergative as well as accusative language. It is classified into an ergative language as the argument of the unmarked transitive verbal P is similarly  treated to the intransitive simple argument depending on how the constituents are ordered. The limitation of Lio language is that P and S can be relativised and modified by the emphatic marker. The only P and S which function as pivots allow the noun which coreferences in both the coordinate and subordinate clauses to disappear.
Keywords: structural alternates, verbal serialization, valence, transitivity, mapping, causative and ergative typology.